Surface Design for Immobilization of an Antimicrobial Peptide Mimic for Efficient Anti‐Biofouling. Issue 26 (21st April 2020) - Hasan, Abshar; Lee, Kyueui; Tewari, Kunal; Pandey, Lalit M.; Messersmith, Phillip B.; Faulds, Karen; Maclean, Michelle; Lau, King Hang Aaron
Abstract: Microbial surface attachment negatively impacts a wide range of devices from water purification membranes to biomedical implants. Mimics of antimicrobial peptides (AMPs) constituted from poly( N ‐substituted glycine) „peptoids" are of great interest as they resist proteolysis and can inhibit a wide spectrum of microbes. We investigate how terminal modification of a peptoid AMP‐mimic and its surface immobilization affect antimicrobial activity. We also demonstrate a convenient surface modification strategy for enabling alkyne–azide „click" coupling on amino‐functionalized surfaces. Our results verified that the N‐ and C‐terminal peptoid structures are not required for antimicrobial activity. Moreover, our peptoid immobilization density and choice of PEG tether resulted in a „volumetric" spatial separation between AMPs that, compared to past studies, enabled the highest AMP surface activity relative to bacterial attachment. Our analysis suggests the importance of spatial flexibility for membrane activity and that AMP separation may be a controlling parameter for optimizing surface anti‐biofouling. Abstract : Efficient anti‐biofouling : We show that an archetypical antimicrobial peptoid could retain high activity even with terminal modifications. Immobilization by alkyne–azide „click" coupling on one‐step modified amino‐surfaces was demonstrated. Appropriate spatial separation between immobilized peptoids, rather than increasing surface density, was found to promote both resistance against bacterial attachment and AMP surface activity.